Lived experience and educational research methodology : reflections on the PhD journey - Corbett, Michael (Professor emeritus) (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Most education and social science research methodology texts offer detailed and often prescriptive advice to higher degree students generally following established paradigmatic frameworks for qualitative and/or qualitative research. Lived Experience and Educational Research Methodology: Reflections on the PhD Journey offers instead a set of retrospective narrative accounts of the complex lived process of developing a thesis project in the field of education. Challenging myths, stereotypes and related linear research imaginaries, the focus of this book is both the particular, messy, located research problems that tend to drive education research as well as how differently positioned recent graduates situated their academic writing in relation to their diverse ethical and personal commitments, theoretical and political passions, methodological choices and community membership. Each chapter in this book is a narrative account of the how-did rather than the how-to of qualitative social science dissertation writing in the field of education. Lived Experience and Educational Research Methodology: Reflections on the PhD Journey also demonstrates how doctoral writing reflects both experiential politics, but also geographic location. The authors in this collection are graduates of a small, technologically hybrid, rural-regional doctoral program which is both unique to its place, but also representative of a growing number of non-metropolitan higher degree programs explicitly designed to provide broad access to geographically and populations otherwise marginalized from large and established metrocentric higher education programs"-- Provided by publisher.
Keywords: Education -- Research -- Methodology.; Doctor of philosophy degree.; Education -- Research.; Teacher training.; Education.; elektronické knihy; electronic books